(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The initial compounds 2-morpholinoethan-1-amine. All reagents and solvents used in the synthesis were of reagent grade and employed without additional purification. Yellow powder 2-morpholinoethan-1-amine [Aldrich, purum > 98% (NT)], (0.152g 10 mM) and hydrochloric acid (Aldrich, 35 % in H2O, 99.95%), (2 mL) were mixed in diethyl ether (10 mL) at room temperature to form a 4-(2-ammonioethyl)morpholin-4-ium chloride precursor solution. The solution was heated to 60 0C and kept at this temperature for 10 min.